2021
DOI: 10.3389/feduc.2021.725337
|View full text |Cite
|
Sign up to set email alerts
|

Development of Numeracy and Literacy Skills in Early Childhood—A Longitudinal Study on the Roles of Home Environment and Familial Risk for Reading and Math Difficulties

Abstract: This study examines the direct and indirect effects of home numeracy and literacy environment, and parental factors (parental reading and math difficulties, and parental education) on the development of several early numeracy and literacy skills. The 265 participating Finnish children were assessed four times between ages 2.5 and 6.5. Children’s skills in counting objects, number production, number sequence knowledge, number symbol knowledge, number naming, vocabulary, print knowledge, and letter knowledge wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 101 publications
1
23
1
Order By: Relevance
“…Indeed, the 12 self-report items we used tapped for the most part the same variance as the selected skill assessments. Our prediction based on a more comprehensive self-report was notably better than that reported in studies employing only one yes-or-no selfconcept of ability question (Esmaeeli et al, 2018(Esmaeeli et al, , 2019Khanolainen et al, 2020;Salminen, Khanolainen, et al, 2021), as these studies explained only around 1%-3% of variance in children's reading. Relying on a single self-concept of ability question is problematic because adults inevitably evaluate their reading level by comparing their skills with those of their reference group, which may drastically differ from one adult to another.…”
Section: Is There a Need To Expand Assessment Batteries?contrasting
confidence: 88%
See 1 more Smart Citation
“…Indeed, the 12 self-report items we used tapped for the most part the same variance as the selected skill assessments. Our prediction based on a more comprehensive self-report was notably better than that reported in studies employing only one yes-or-no selfconcept of ability question (Esmaeeli et al, 2018(Esmaeeli et al, , 2019Khanolainen et al, 2020;Salminen, Khanolainen, et al, 2021), as these studies explained only around 1%-3% of variance in children's reading. Relying on a single self-concept of ability question is problematic because adults inevitably evaluate their reading level by comparing their skills with those of their reference group, which may drastically differ from one adult to another.…”
Section: Is There a Need To Expand Assessment Batteries?contrasting
confidence: 88%
“…Importantly, both self-reports and parental skill assessments showed similar predictive power for children's reading; the two methods only slightly complemented each other and thus could be used interchangeably. Moreover, self-reports with multiple items provided a notably better FR estimation in our study than self-reports with a single item employed in previous studies (Esmaeeli et al, 2018(Esmaeeli et al, , 2019Khanolainen et al, 2020;Salminen, Khanolainen, et al, 2021). FR estimations may be further improved by adding tests for cognitive skills or more self-report items.…”
Section: Discussionmentioning
confidence: 50%
“…The associations documented between parental education and children's reading performance have also implications for understanding of the role of home learning environments. Highly educated parents are likely to have different types of resources that contribute to providing their children rich learning environments, involving more literacy activities of high quality (e.g., Chiu & McBride-Chang, 2006;Khanolainen et al, 2020;Salminen et al, 2021;Sirin, 2005), which have been shown to have long-term effects on children's reading achievements (e.g., Bus et al, 1995;Mol & Bus, 2011;Scarborough & Dobrich, 1994;Sénéchal & LeFevre, 2002;Torppa et al, 2022). It may be speculated that varied and enriching father-child literacy activities may benefit children and at-risk boys in particular.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the predictive effect of parental education on children's reading skills is not clear. One possible explanation is that parents with higher education levels provide a richer home learning environment for their children (e.g., Chiu & McBride-Chang, 2006;Khanolainen et al, 2020;Salminen et al, 2021;Sirin, 2005), which supports language and literacy development (e.g., Sénéchal, 2006). On the other hand, as reading difficulties run in families mainly through the genetic route (e.g., Lohvansuu et al, 2021;Snowling & Melby-Lervåg, 2016), the association between parental education and child's skills may be linked to deficiencies in parents' reading skills impacting both parents' educational levels and children's higher risk for reading difficulties.…”
Section: Parental Education and Children's Reading Skillsmentioning
confidence: 99%
“…Numbers are always associated with time, distance, money, and size. In order to be able to interact and transact in daily life, it is necessary to have numeracy literacy skills (Salminen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%